Perilaku Masyarakat Sebelum dan Sesudah Sosialisasi tentang Bantuan Hidup Dasar (BHD) - Heriati Berutu; Robert Harnat Silalahi (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effectiveness of the community in knowledge and behavior in carrying out essential life support (BHD). The research method used was quantitative by using a Quasi-Experimental research design method; the research respondents were 32. The research was conducted in Sitinjo II Dairi Village, North Sumatra. The study results using the Mc Nemar Exact Sig statistical test, (2-tailed) 0.004 with a p-value <0.05. In conclusion, the socialization of essential life support (BHD) influences community behavior regarding BHD in Sitinjo II Village, Kec. Sitinjo Kab. Dairy. Keywords: BHD, Knowledge, Community Behavior, Outreach